Jilbab dan Kebebasan Beragama - Ramadhani, Dwika Ayu (Maliki Interdisciplinary Journal, 2025)
This article examines the perspective of international human rights law on the wearing of the hijab by Muslim women as a means of expressing their religious beliefs. The hijab is a symbol of devotion to God and is an integral aspect of Islam. In many countries, laws regarding the hijab raise human rights concerns, particularly regarding equality, anti-discrimination and religious freedom. The article examines the theological stance of the hijab, the ways in which hijab bans in Western countries exacerbate prejudice against Muslim women, and the laws governing the use of the hijab in the EU. It concludes that there is no legitimate international legal justification for banning the hijab as it would violate religious freedom and could exacerbate prejudice against Muslim women.